The - 1 - The importance of sonographic evaluation of muscle depth and thickness prior to the 'tiny percutaneous needle biopsy' - Tereza Jandova; Danilo Bondi; Vittore Verratti; Marco Narici; Michal Steffl; Tiziana Pietrangelo (PAGEPress Publications, 2020)
Biopsy of human skeletal muscle tissue is a widely used method in many research studies, where 'the tiny percutaneous needle biopsy' (TPNB) is one of the relatively simplest and safest procedures currently available. By using and contrasting ultrasound images of vastus lateralis of young and elderly subjects, this work highlights further the safety aspects of TPNB and stresses the importance of prior ultrasound evaluation of muscle depth and thickness in order to prevent wrong muscle group or tissue sampling in subsequent laboratory analyses.